Development Strategy Of Spring Roll Gang Lombok Semarang Based On SWOT Analysis - Widani, Ni Nyoman; Pramudia, Heru (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Lumpia Gang Lombok Semarang is a cultural and culinary icon with over a century of history, celebrated for its traditional recipes blending Chinese and Javanese influences. This study analyzes the development strategies for Lumpia Gang Lombok using SWOT analysis to address challenges such as limited digital presence, operational inefficiencies, and competition from modern food businesses. The findings highlight the business's strengths, including its authenticity and cultural significance, while identifying opportunities for growth through digital marketing, product diversification, and collaborations with tourism stakeholders. Strategic recommendations emphasize balancing tradition with modernization to enhance market competitiveness and preserve cultural heritage. The study contributes to the discourse on culinary tourism and the sustainability of traditional food businesses in Indonesia.